Making sense of child sexual exploitation : exchange, abuse and young people / Sophie Hallett. - Hallett, Sophie (Policy Press, 2017)
Providing fresh insight into child sexual exploitation (CSE), this book uses the voices of children and young people who have experienced sexual exploitation, and the practitioners who have worked with them, to challenge the dominant discourse around CSE.